A method of verifying partition congruences by symbolic computation. (May 2021) - Radu, Cristian-Silviu; Smoot, Nicolas Allen
Abstract: Conjectures involving infinite families of restricted partition congruences can be difficult to verify for a number of individual cases, even with a computer. We demonstrate how the machinery of Radu's algorithm may be modified and employed to efficiently check a very large number of cases of such conjectures. This allows substantial evidence to be collected for a given conjecture, before a complete proof is attempted.